2000
DOI: 10.1523/jneurosci.20-12-04423.2000
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Synaptic Currents and Glutamate Spillover at the Parallel Fiber to Stellate Cell Synapse

Abstract: Although neurons often fire in bursts, most of what is known about glutamate signaling and postsynaptic receptor activation is based on experiments using single stimuli. Here we examine the activation of ionotropic glutamate receptors by bursts at the parallel fiber to stellate cell synapse. We show that brief stimulus trains generate prolonged AMPA receptor (AMPAR)- and NMDA receptor (NMDAR)-mediated EPSCs recorded in whole-cell voltage clamp. These EPSCs contrast with the rapid AMPAR-mediated EPSC evoked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
223
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(239 citation statements)
references
References 63 publications
13
223
0
3
Order By: Relevance
“…In pilot studies, PDC efficacy in increasing glutamate in the cleft was verified on secondorder baroreceptor NTS neurons by the following: 1) PDC in the perfusate increased the decay time constant for TS-evoked glutamatergic excitatory postsynaptic currents by 34% (2.7 Ϯ 0.3 to 3.7 Ϯ 0.6 ms, n ϭ 3); and 2) increased the peak amplitude of the inward current evoked by application of exogenous glutamate (300 M) with NBQX, AP5, bicuculline, and TTX in the perfusate by 146% (146.3 Ϯ 39.8 pA, n ϭ 4 vs. 59.5 Ϯ 7.2 pA, n ϭ 5; one-tail t-test, P ϭ 0.034), consistent with previous findings (Carter and Regehr 2000). The neurons were initially held at their own resting membrane potentials (Ϫ50.5 Ϯ 1.3 mV) and then recorded in current-clamp mode.…”
Section: Endogenous Glutamate Releasesupporting
confidence: 90%
“…In pilot studies, PDC efficacy in increasing glutamate in the cleft was verified on secondorder baroreceptor NTS neurons by the following: 1) PDC in the perfusate increased the decay time constant for TS-evoked glutamatergic excitatory postsynaptic currents by 34% (2.7 Ϯ 0.3 to 3.7 Ϯ 0.6 ms, n ϭ 3); and 2) increased the peak amplitude of the inward current evoked by application of exogenous glutamate (300 M) with NBQX, AP5, bicuculline, and TTX in the perfusate by 146% (146.3 Ϯ 39.8 pA, n ϭ 4 vs. 59.5 Ϯ 7.2 pA, n ϭ 5; one-tail t-test, P ϭ 0.034), consistent with previous findings (Carter and Regehr 2000). The neurons were initially held at their own resting membrane potentials (Ϫ50.5 Ϯ 1.3 mV) and then recorded in current-clamp mode.…”
Section: Endogenous Glutamate Releasesupporting
confidence: 90%
“…It has been demonstrated in many synapses that the inhibition of uptake of synaptically released transmitter causes spillover of transmitter to neighboring synapses (Rossi and Hamann, 1998;Carter and Regehr, 2000;Diamond, 2001;Clark and Cull-Candy, 2002;DiGregorio et al, 2002;Takayasu et al, 2004). The results shown in this study can also be reasonably explained by the hypothesis that glutamate spillover causes both pharmacologically induced slow-rising and mutant atypical CF-EPSCs.…”
Section: Glutamate Spilloversupporting
confidence: 72%
“…K716A-EOS signal amplitude increased with the time-integral of the EPSC, showing the dependence of extrasynaptic glutamate dynamics on the density of stimulated PFs (Fig. 3C) (8,11,30). It is thus strongly suggested that glutamate released from neighboring synapses can be integrated in the extrasynaptic space.…”
Section: Extrasynaptic Glutamate Dynamics Are Locally Induced By a Smallmentioning
confidence: 83%